A review on recent advances and progress in Mo2C@C: A suitable and stable electrocatalyst for HER. (26th April 2023) - Mir, Rameez Ahmad; Upadhyay, Sanjay; Pandey, O.P.
Abstract: In this review, the environmental issues and the energy crisis caused due to overuse of diminishing fossil fuels have been introduced and discussed. The need for new renewable, non-carbon emission energy sources and the importance of hydrogen (H2 ) as clean and efficient energy generated via hydrogen evolution reaction (HER) through electrochemical water splitting is discussed. The role of an efficient electrocatalyst for HER has been highlighted. The requirement of low-cost, efficient, and durable electrocatalysts for HER to replace the costly platinum (Pt) electrocatalysts is introduced. The importance of nano transition metal carbides (TMCs), especially molybdenum carbide (Mo2 C), as an efficient and stable electrocatalyst has been discussed in detail. The progress and advances to improve the electrocatalytic performance of nano Mo2 C on the basis of synthesis, size, shape, and carbon support in different forms have been presented. The role of different carbon species over Mo2 C on HER activity has been discussed. The importance of nitrogen (N) doping within the carbon structure encapsulating Mo2 C particles to improve the HER activity has been highlighted. The importance of in-situ developed surface carbon over Mo2 C has been discussed in detail. The utilization of waste carbon materials to address the environmental issues caused due to non-biodegradable wastes is also discussed. In the end, the future scope has been highlighted to commercialize Mo2 C as a low-cost electrocatalyst for hydrogen production through HER. Highlights: Advances and progress in carbon-supported Mo2C to improve HER performance. Role of carbon support on HER activity. Role of In-situ developed surface carbon with other carbon-supported materials. Scope of the utilization of carbonaceous waste as a carbon source. Outlines to carry the future research for commercial application of Mo2 C.